Principal Managerial in Improving Teacher Performance at Senior High School - Novarina Novarina; Nasir Usman; Murniati Murniati (STAI Hubbulwathan Duri, 2023)
One of the principal's duties is as a manager. Principals must have plans, strategies, ways of communicating so that teacher performance can be good. The objectives of the study were (1) to determine the managerial principles in improving teacher performance and (2) to find out the obstacles faced by a principal in improving teacher performance. The research uses qualitative methods. Methods for gathering data are performed in natural environments. The school's administration and faculty members provided the research participants. Interviews and direct observation were used as data-gathering methods. Two Banda Aceh high school's administration and teachers participated in the study. Descriptive qualitative analysis is employed, and the data processing procedures of reduction, display, conclusions, and verification are carried out. From the results of the study, it was found that (1) the planning carried out by the principal in improving the performance of teachers was in accordance with the conceptual planning steps, namely identifying problems, formulating goals, and coordinating with staff about the program being implemented will be implemented. (2) the strategies adopted by school principals to improve teacher performance are different. The strategy of the principal of senior high school A in Banda Aceh is information disclosure; that is, every staff must know what agenda will be implemented at the school, while senior high school B is coaching through supervision activities. Supporting factors that can improve teacher performance are teacher performance abilities, work motivation, school culture that is developed, and applied leadership as well as a conducive and safe school climate.